Peran Guru Sandaran dalam Revitalisasi Tata Kelola Manajemen Pesantren Ma’had Al-Zaytun Menuju Kemandirian Santri - Baqiya Aini Wahyu Ningtyas; Novia Rahma Aulia; Meity Suryandari (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the role of mentor teachers in revitalizing the management of Ma’had Al-Zaytun toward fostering student independence in the digital age. The study employs a descriptive qualitative approach, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The research informants consist of mentor teachers and students directly involved in the boarding school-based mentoring system. The results indicate that the management of the Islamic boarding school at Ma’had Al-Zaytun is implemented in a structured manner through the boarding school system and the “one-pipe education system” concept, which integrates religious education, science, information technology, and life skills into a single sustainable system. In its implementation, the mentor teacher plays a strategic role not only as a character guide and informal educator but also as a digital system mediator, a communication liaison with students’ guardians, and a supervisor of students’ expenditures through a cashless system. Mentor teachers also play a role in monitoring technology use, managing student information, and fostering students’ digital literacy and financial literacy through the cashless transaction system. This study confirms that the success of revitalizing the governance of modern Islamic boarding schools is determined not only by systems and leadership but also by the effectiveness of the “guru sandaran” as the primary implementers of character development and digital transformation within the boarding school environment.